Establishing Reference Values for Isometric Knee Extension and Flexion Strength - Šarabon, Nejc; Kozinc, Žiga; Perman, Mihael (Frontiers in Physiology, 2021)
Single-joint isometric and isokinetic knee strength assessment plays an important role in strength and conditioning, physical therapy and rehabilitation. The literature, however, lacks absolute reference values. We systematically reviewed the available studies that assessed isometric knee strength. Two scientific databases (PubMed and PEDro) were searched papers published from the inception of the field to the end of 2019. We included studies that involved participants of both genders and different age groups, regardless of the study design, that involved isometric knee extension and/or flexion measurement. The extracted data was converted to body-mass-normalized values. Moreover, the data was grouped according to the knee angle condition (extended, mid-range and flexed). A meta-analysis was performed on 13893 participants from 411 studies. In adult healthy males, the pooled 95% confidence intervals (CI) for knee extension were 1.34-2.23 Nm/kg for extended knee angle, 2.92-3.45 Nm/kg for mid-range knee angle and 2.50-3.06 Nm/kg for flexed knee angle, while the CIs for flexion were 0.85-1.20 Nm/kg, 1.15-1.62 Nm/kg and 0.96-1.54 Nm/kg, respectively. Adult females consistently showed lower strength than adult male subgroups (e.g., the CIs for knee extension were 1.01-1.50 Nm/kg, 2.08-2.74 Nm/kg and 2.04-2.71 Nm/kg for extended, mid-range and flexed knee angle condition). Older adults consistently showed lower values than adults (e.g. pooled CIs for mid-range knee angle were 1.74-2.16 Nm/kg (male) and 1.40-1.64 Nm/kg (female) for extension, and 0.69-0.89 Nm/kg (male) and 0.46-0.81 Nm/kg (female) for flexion). Reliable normative for athletes could not be calculated due to limited number of studies for individual sports.